1978
DOI: 10.1172/jci108924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Proteolytic Enzymes on the Binding of Cobalamin to R Protein and Intrinsic Factor

Abstract: A B S T R A C T Cobalamin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(42 citation statements)
references
References 18 publications
6
36
0
Order By: Relevance
“…Cbl-analogues were not revealed in cow milk and the amount of TC-Cbl (3 nmol per liter) was quite sufficient to satisfy the demands of daily intake for man (1 nmol) [35]. The instability of TC-Cbl at pH 2 guaranties the liberation of Cbl in acidic medium of human stomach and its binding to human IF and HC [37,38]. It means that cow milk is an appropriate source of B~2 for man.…”
Section: Discussionmentioning
confidence: 99%
“…Cbl-analogues were not revealed in cow milk and the amount of TC-Cbl (3 nmol per liter) was quite sufficient to satisfy the demands of daily intake for man (1 nmol) [35]. The instability of TC-Cbl at pH 2 guaranties the liberation of Cbl in acidic medium of human stomach and its binding to human IF and HC [37,38]. It means that cow milk is an appropriate source of B~2 for man.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the genes for IF and HC are located in chromosome 22 (7,8), whereas the gene for TC is located in chromosome 11 (9). Human IF contains 399-aa residues plus Ϸ15% carbohydrate, giving it a molecular mass of Ϸ60 kDa, as observed by gel filtration (10)(11)(12)(13). All three proteins promote Cbl entry through endocytosis involving distinct cell surface receptors (5,(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…In addition, other concurrent (14) and more recent in vivo studies (17) demonstrated that IF free of Cbl remains biologically, immunologically, and physicochemically unaltered, whereas the R protein(s) are being degraded during normal intraluminal transport. These latter observations supported the thesis (16) that in EPI the R protein(s) are not subject to degradation and therefore the entire fraction of Cbl bound to these nonfunctional proteins will not be absorbed (14,16,17). Recent studies in Rothenberg's laboratory (18) indicated that bile effectively sequesters Cbl from IF to nonfunctional binders and that this process can be reversed after treatment with proteases (18).…”
Section: Introductionmentioning
confidence: 58%
“…It appears likely: (a) that the impairment of Cbl absorption in EPI is a result of a biochemical defect that supervenes somewhere between the gastric and the ileal wall phase of the Cbl transport, i.e., during the intraluminal phase of Cbl transport and; (b) that this defect does not alter the function of IF as such but rather the mode of transport of Cbl itself. These possibilities have recently been fully appreciated by Allen et al (16), who speculated that the presence of undegraded R-type Cbl-binding protein(s) (R protein,2 cobalophilin, non-IF, etc.) in the intestinal lumen can inhibit the ileal absorption of the vitamin, and showed by in vitro studies that purified pancreatic proteases can degrade R proteins but not IF (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation